Vulvar Dermatofibrosarcoma protuberance in Iran and a narrative review of literature: A first case report - Mohsen Mohammadi; Haniyeh Esfandiar; Nazanin Saeedi zand; ali shaabani; Firuze Esmaeilzade (Babol University of Medical Sciences, 2024)
Background: Pott's Puffy tumor (PPT) is a complicated frontal sinusitis that is also described as frontal bone osteomyelitis and a localized sub periosteal abscess. Early diagnosis and immediate active treatment are necessary to prevent severe neurologic sequelae. Case Presentation: Here, we report on a case of Pott's puffy tumor in a previously healthy 13-year-old girl with a worsening headache and swelling of the frontal bone accompanied by vomiting and fever. Magnetic resonance imaging revealed osteomyelitis of the frontal bone. A foreign body was discovered and removed via endoscopy which was then followed by 6 weeks of parenteral and enteral antibiotic therapy, resulting in resolution of all symptoms. Conclusion: A complete history in terms of trauma and insect bite or foreign body in the nose is paramount for a correct diagnosis, and performing a full examination of ear, nose and throat (ENT) to rule out a foreign body is advised.